Nyctalus noctula - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Nyctalus noctula (Schreber 1774) [Vespertilio] noctula Schreber 1774, Die Saugethiere, Vol. 1: 166. Type Locality: France. Vernacular Names: Noctule. Synonyms: Nyctalus macuanus Peters 1852. Subspecies:: Subspecies Nyctalus noctula subsp. noctula Schreber 1774 Subspecies Nyctalus noctula subsp. labiata Hodgson 1835 Subspecies Nyctalus noctula subsp. lebanoticus Harrison 1962 Subspecies Nyctalus noctula subsp. mecklenburzevi Kuziakin 1934 Distribution: Europe and S Scandinavia to Urals and Caucasus; Turkey to Israel and Oman; W Turkmenistan, W Kazakhstan, Uzbekistan, Kyrgyzstan, and Tajikistan to SW Siberia, Himalayas, south to Burma, Vietnam, and W Malaysia; possibly Algeria. A record from Mozambique is dubious (Koopman, 1993, 1994). Conservation: IUCN 2003 and IUCN / SSC Action Plan (2001) – Lower Risk (lc). Discussion: Formerly included furvus and velutinus , but these appear to be distinct; see Yoshiyuki (1989), but also see Corbet (1978 c ) and Corbet and Hill (1992). Does not include sinensis , which was recognized as a senior synonym of Vespertilio superans by Horácek (1997). Reviewed in part by Harrison and Bates (1991), Bates and Harrison (1997), and Horácek et al. (2000). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Chiroptera - Family Vespertilionidae, pp. 451-529 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 472, DOI: 10.5281/zenodo.7316519